COVID-19 Coinfection with Mycobacterium abscessus in a Patient with Multiple Myeloma - Jose A. Rodriguez; Charles Bonnano; Pratik Khatiwada; Alejandra A. Roa; Daniel Mayer; Paula A. Eckardt (Case Reports in Infectious Diseases)
Background. Coronavirus disease (COVID-19) is a worldwide pandemic causing multiple fatalities and morbidities worldwide. We report a case of severe pneumonia causing acute respiratory distress syndrome due to a coinfection with SARS-CoV-2 and Mycobacterium abscessus in an elderly patient with multiple myeloma in Florida, USA. Case Presentation. An 84-year-old male with a medical history significant for multiple myeloma not in remission was sent to the emergency department to rule out COVID-19 infection prior to continuing his chemotherapy sessions. At presentation, he had nonspecific mild symptoms and an unremarkable physical examination. He had significant blood test findings including serum lactate dehydrogenase 373 U/L, high sensitive C-reactive protein 17.40 mg/l, and ferritin 415 ng/ml. Xpert-SARS-CoV-2 was positive. Chest radiograph revealed patchy areas of interstitial infiltrates in mid to lower lung zones. During his hospitalization course, his oxygenation deteriorated, requiring mechanical intubation. Repeat chest radiograph showed worsening bilateral infiltrates. He was started on broad-spectrum antibiotics and eventually weaned off mechanical intubation and extubated. On the 11th day of admission, he was found to be bradycardic and in shock, and he was reintubated. His labs showed worsening inflammatory markers along with kidney dysfunction to the point of requiring renal replacement therapy. He received both convalescent plasma and remdesivir for treatment of COVID-19 pneumonia. Eventually, repeat blood cultures came back positive for the growth of acid-fast beaded bacilli. While awaiting final culture and sensitivity reports, his antibiotics were upgraded to cover possible nocardia infection. Repeat blood and sputum cultures resulted in growth of AFB bacilli Mycobacterium abscessus 1 week after. Conclusions. This case report highlights the importance of keeping a broad differential and considering multiple coinfections, including atypical ones during this COVID-19 pandemic, such as the one that was discussed above, Mycobacterium abscessus, in order to provide goal-directed therapy.